2018
DOI: 10.1175/jcli-d-17-0240.1
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Precipitation Change: An Energetic Understanding

Abstract: The response of the hydrological cycle to climate forcings can be understood within the atmospheric energy budget framework. In this study precipitation and energy budget responses to five forcing agents are analyzed using 10 climate models from the Precipitation Driver Response Model Intercomparison Project (PDRMIP). Precipitation changes are split into a forcing-dependent fast response and a temperature-driven hydrological sensitivity. Globally, when normalized by top-of-atmosphere (TOA) forcing, fast precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 65 publications
(72 reference statements)
15
93
0
Order By: Relevance
“…The difference in 10‐m wind speed between two simulations is nearly constant over time. The differences in climate variables, which increase with warming, are consistent with previous studies that reported increased surface temperatures and an intensified water cycle with warming (Boucher et al, ; Richardson et al, ). The anthropogenic effect on surface radiation is less obvious, although model‐based studies have reported a decrease in shortwave radiation at the surface with warming (Richardson et al, ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The difference in 10‐m wind speed between two simulations is nearly constant over time. The differences in climate variables, which increase with warming, are consistent with previous studies that reported increased surface temperatures and an intensified water cycle with warming (Boucher et al, ; Richardson et al, ). The anthropogenic effect on surface radiation is less obvious, although model‐based studies have reported a decrease in shortwave radiation at the surface with warming (Richardson et al, ).…”
Section: Resultssupporting
confidence: 91%
“…The differences in climate variables, which increase with warming, are consistent with previous studies that reported increased surface temperatures and an intensified water cycle with warming (Boucher et al, ; Richardson et al, ). The anthropogenic effect on surface radiation is less obvious, although model‐based studies have reported a decrease in shortwave radiation at the surface with warming (Richardson et al, ). To the best of our knowledge, there is no observational evidence of a long‐term decrease in surface shortwave radiation with large decadal variability (Wild, ).…”
Section: Resultssupporting
confidence: 91%
“…This matches the reduction in the surface latent heat flux associated with evaporation (Table ) and is consistent with the stabilizing influence of BC on the atmosphere. The reductions in global precipitation are also consistent with the requirement to rebalance the atmosphere's heat budget (e.g., Myhre et al, ; Richardson et al, ), which is explored later in section . The global‐mean and local changes in precipitation are almost entirely due to changes in convective (parameterized) precipitation, with weak or mostly insignificant changes in stratiform precipitation (Figure S5).…”
Section: Resultssupporting
confidence: 64%
“…This matches the reduction in the surface latent heat flux associated with evaporation (Table 2) and is consistent with the stabilizing influence of BC on the atmosphere. The reductions in global precipitation are also consistent with the requirement to rebalance the atmosphere's heat budget (e.g., Myhre et al, 2018;Richardson et al, 2018),…”
Section: Precipitationsupporting
confidence: 67%
See 1 more Smart Citation